Epistemology of music formation: reflections for its constitution (Orfeu, 2024)
The article’s aims to reflect about a theory of teaching formation in music based on the references utilized in rese-arches on the fields of Music and Musical Education about this subject. Based on interinstitutional research that studied 220 academic works published in the last 30 years, and adopting the bricolage methodology as a procedure, theoretical perspectives of Music and Musical Edu-cation which characterized the docent formation come to discussion, with the analysis of the impacts for its different conceptions. The results were studied by four categories seen as dimentions to understand the advance of the concepts in the area. Thereby it was possible to identify a certain repertory of knowledge which has been discussed and theorized, that contributes to the constitution of a docent culture in music. Neverthe-less, it remains an alert for the necessity that other possibilities must be explored, mostly, based on the theories which were born from Music itself.
Keywords: docent knowledge in music; supervised internship in music; docent formation in music; licentiate in music